(untitled) (Berlin, 2005)
This book constitutes the thoroughly refereed proceedings of the Second International Joint Conference on Natural Language Processing, IJCNLP 2005, held in Jeju Island, Korea in October 2005. The 88 revised full papers presented in this volume were carefully reviewed and selected from 289 submissions. The papers are organized in topical sections on information retrieval, corpus-based parsing, Web mining, rule-based parsing, disambiguation, text mining, document analysis, ontology and thesaurus, relation extraction, text classification, transliteration, machine translation, question answering, morphological analysis, text summarization, named entity recognition, linguistic resources and tools, discourse analysis, semantic analysis NLP applications, tagging, language models, spoken language, and terminology mining.
Keywords: Natural language processing (Computer science),Xử lý ngôn ngữ tự nhiên (Khoa học máy tính)